CBE690: Quality management in food industry / College of Engineering - UiTM, College of Engineering (2018)
This course covers the principles and approaches that can be implemented in food industry to meet the quality standards. This includes food safety, the related regulations and guidelines. Related issues in food industry such as halal and genetically modified food also being discussed.